Deviant Behaviour - Acus, Arūnas (Sociologija. Mintis ir veiksmas, 2015)
The aim of this article is to discuss the concept of deviant behaviour, which has become widely used in the last few decades. The author suggests that deviant behaviour might be understood as a polidetermined phenomenon which reflects the interaction between multidimensional factors. These factors include macro-sociological, social-psychological and individual, personal factors. The article focuses the attention on the individual level and discusses the ideas of symbolic interactionism for understanding deviant behaviour. The author argues for a definition of deviant behaviour, central to which is the notion of interpretative self-understanding.
Keywords: deviant behaviour; person; symbolic interactionism